The impact of play-informed caregiver-implemented home-based intervention on the academic learning outcomes for HIV positive children (aged 5 years to 8 years) on Antiretroviral Therapy (ART) living in low income conditions: a randomized control trial - Otto, Caraleigh (Division of Occupational Therapy, 2017)
BACKGROUND: The academic learning of HIV positive children is often negatively impacted by cognitive and learning deficits associated with HIV, and usually leads to poor performance at school. Occupational therapy, a profession that promotes and enhances participation in meaningful occupations, has yet to demonstrate its impact in promoting the occupation of academic learning in HIV positive children on ART. OBJECTIVES: This study investigates and compares the impact of two occupational therapy interventions; conventional one-on-one occupational therapy (control group) and play-informed caregiver-implemented home-based intervention (PICHIBI) (experimental group), in promoting academic learning for HIV positive children aged 5 to 8 year olds on ART. METHODS: The research project followed a pragmatic, single-blinded, randomised baseline, mid and post-test control-group design. From a possible population of 60 dyads who attend the Groote Schuur Hospital (Cape Town, South Africa) ARV clinic, 27 child-caregiver dyads (n=27) were recruited. One dyad was excluded from the study, due to home circumstances, leaving 26 dyads that went through the randomisation and allocation process into the two intervention groups. Randomisation was carried out by a central computer system, before the start of the intervention period. The final total sample (n=23) completed the intervention, a slight decrease from the recruited sample size. Four dyads were lost to follow up after the baseline test. This resulted in 12 dyads in the control group and 11 dyads in the experimental group. Baseline, mid (after 5 months of the intervention) and post (after 10 months of intervention) test data was collected using the Griffiths Mental Developmental Scales-Extended Revised (GMDS-ER) and the short form Beery-Buktenica Visual Motor Integration test , 5th edition (Beery-VMI) as outcome measures. RESULTS: Following randomisation there were minimal variations in the baseline demographics and measurements for the two groups, with the exception of a significant difference in time on ART (p=.021). The majority of each group had suppressed viral loads. The total sample showed delays in all the performance components linked to academic learning at baseline, that is, low for visual motor integration and visual perception, below average for motor coordination, borderline delay in language, and practical reasoning, and low average in eye hand co-ordination, performance and the overall level of functioning (general quotient). Severe delays (<70) were detected in the control group at baseline for visual perception, and at post test for language. Average scores (90-109) at post test for visual perception and motor co-ordination were only seen in the experimental group. No statistical significance was noted for between-group differences at baseline, mid and post test. For within-group changes, statistically significant improvements were observed in the following performance components linked to academic learning: in the experimental group, visual motor integration from baseline to mid test (p=.019); in the control group, visual perception from baseline to post test (p=.009) and visual perception baseline to mid test (p=.001), and in performance from baseline to mid test (p=.027). Following interventions the overall GMDS-ER quotient scores for both groups improved with 70% of the experimental group and 58.3% of the control group scoring more than -2 z-score. In the total sample, the level of severe delay at baseline (68.2%) improved to only 8 out of the 23 (36.4%) of the total sample showing a severe overall delay post intervention. These scores still classified the groups as below average (90-109) under the GMDS-ER UK classifications. Despite these scores, 95.7% of the total sample progressed to the next grade during intervention, with only one child repeating a grade. CONCLUSION: Improvements were seen in both groups from baseline to post test. The advantage of PICHIBI however is that it is better suited for expanding access to occupational therapy services in a context where the occupational therapist/patient ratio in the public health sector is low. The continued underperformance of both groups in academic learning outcomes post intervention, displays the need for ongoing intervention for HIV-infected school going children. This information will inform occupational therapy practice, guide policies and legislations relating to academic learning for children with HIV on ART, in South Africa. It is recommended that future research look into using a larger sample size for generalisability of findings, consider conducting a longitudinal study linking results with school report outcomes and comparing the effects of the intervention at various levels of health care.